atio Decidendi dalam Menolak Putusan Gugatan Perceraian berdasarkan Putusan nomor 1319/PDT.G/PA.TBN di Pengadilan Agama Tuban dalam Perspektif Keadilan - Ni'am, Khafaz Syah Fajar (Taruna Law: Journal of Law and Syariah, 2024)
Marriage is an innate and inner bond between a man and a woman as husband and wife. In a marriage, various problems related to husband and wife will arise, so they are required to understand each other in all things. This research includes a type of empirical juridical research, namely examining the applicable legal provisions and what happens in reality in society, the researcher takes a location at the Religious Court, namely the Tuban Religious Court, as for the method used in analyzing the data using the descriptive analysis method. Based on the results of the study, there is a conclusion that can be drawn that based on Case Number 1319/Pdt.G/Pa.Tbn of 2023 there was a quarrel that lasted continuously which led to the separation of residences, Legal consequences after the decision of Case Number 1319/Pdt.G/Pa.Tbn of 2023 if the lawsuit is rejected then the wife still remains the official wife, then from the perspective of justice to Decision Number: 1319/Pdt.G/Pa.Tbn of 2023 is to file a new lawsuit, witha record of evaluating and improving the lawsuit as based on the Jurisprudence of the Supreme Court of the Republic of Indonesia Number 110/K/KG/1992 dated July 23, 1993 which was used as a reference in the National Working Meeting (Rakernas) of the Supreme Court of the Republic of Indonesia in 2007. For the parties, it is necessary before and when entering into a legal relationship with marriage, it is necessary to consider and implement the purpose of marriage as per Law No. 1 of 1974 concerning marriage. Although the judge decides to use the applicable legal system when deciding the case, the judge can use his conscience by strengthening his or her suspicion about the consequences of disputes and quarrels that occur in a-quo cases as per the jurisprudence of the Supreme Court of the Republic of Indonesia Number 299/K/AG/2003 dated June 8, 2005.